(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
We do need unrealistic optimism. The darkness of a realistic view can throw the light into greater relief, making experience richer. In dark times our goal should not be the light at the end of the tunnel but to illuminate its passage, so humankind can bear more reality. Life does not need a happy ending to be a great story.